Electrochemical Cell Chips Based on Functionalized Nanometals - El-Said, Waleed Ahmed; Yoon, Jinho; Lee, Sang-Nam; Choi, Jeong-Woo (Frontiers in Chemistry, 2021)
The electrochemical technique is one of the most accurate, rapid, and sensitive analytical assays, which becomes promising techniques for biological assays at a single-cell scale. Nanometals have been widely used for modification of the traditional electrodes to develop highly sensitive electrochemical cell chips. The electrochemical cell chips based on the nanostructured surface have been used as label-free, simple, and nondestructive techniques for in vitro monitoring of the effects of different anticancer drugs at the cellular level. Here, we will provide the recent progress in fabrication of nanopatterned surface and cell-based nanoarray, and discuss their applications based on electrochemical techniques such as detection of cellular states and chemicals, and non-destructive monitoring of stem cell differentiation.